Chemical Characteristics of PM10 at Background Stations of Central and Eastern China in 2016-2017 - Jiao Jian; Jia Xiaofang; Yan Peng; Cao Fang; Fang Dongqing; Ma Qianli; Yu Dajiang; Chu Jinhua (应用气象学报)
The characteristics of PM10 and its chemical composition from December 2015 to December 2017 are studied at three regional atmospheric background stations (Longfengshan, Lin'an, and Jinsha) in central and eastern China. The water-soluble ions (F-, Cl-, NO3-, SO42-, PO43-, Na+, K+, NH4+, Ca2+, Mg2+), carbon-containing compounds (OC, EC) and main elements in PM10 samples are analyzed. The average PM10 concentration at Lin'an (62.2±36.6 μg·m-3) during the whole period is the highest, followed by Jinsha (57.6±31.8 μg·m-3), and that at Longfengshan (57.5±55.3 μg·m-3) is the lowest. At those stations, the annual PM10 mass concentrations are lower than the national second-level air quality standard. The concentrations of PM10 in 2016-2017 show a downward trend, with the reductions of concentrations about 29.3% at Lin'an and 26.2% at Jinsha compared with the results during the year of 2013.The concentrations of SO42-, NO3-, and NH4+ during the whole period are 9.9, 8.2 μg·m-3 and 3.7 μg·m-3 at Lin'an, and 10.2, 6.7 μg·m-3 and 2.6 μg·m-3 at Jinsha, respectively, which are all higher than those at Longfengshan, with the average concentrations of 5.9 μg·m-3 for SO42-, 4.9 μg·m-3 for NO3-, and 2.1 μg·m-3 for NH4+. However, the ratio of NO3-/SO42- at Longfengshan and Lin'an are relatively higher. The concentrations of OC and EC during the whole period are 10.1 μg·m-3 and 2.7 μg·m-3 at Longfengshan, 6.1 μg·m-3 and 3.1 μg·m-3 at Lin'an, and 4.7 μg·m-3 and 2.3 μg·m-3 at Jinsha. Compared to the year of 2013, the concentrations of SO42-, NH4+ and OC during the whole period decrease by 38.1%, 26.0%, and 55.6% at Lin'an, respectively, and decrease by 46.3%, 51.9%, and 44.7% at Jinsha, while the concentrations of NO3- increase by 12.3% and 15.5% at Lin'an and Jinsha, respectively. The concentrations of EC decreases by 27.9% at Lin'an, but increases by 4.5% at Jinsha. The ratio of NO3-/SO42- increase obviously at all the stations, which indicates the increases of nitrate aerosols, due to the continuously control of coal combustion emissions and increase of car ownership.The seasonal concentrations of PM10, NO3-, EC and the ratio of NO3-/SO42- are lowest in summer at three stations. Meanwhile, the mass concentrations of SO42-, NO3- and NH4+ are basically higher in winter than in other seasons.